Signaling Lymphocytic Activation Molecule Family Member 7 Engagement Restores Defective Effector CD8+ T Cell Function in Systemic Lupus Erythematosus. Issue 5 (May 2017) - Comte, Denis; Karampetsou, Maria P.; Yoshida, Nobuya; Kis‐Toth, Katalin; Kyttaris, Vasileios C.; Tsokos, George C.
Abstract : Objective: Effector CD8+ T cell function is impaired in systemic lupus erythematosus (SLE) and is associated with a compromised ability to fight infections. Signaling lymphocytic activation molecule family member 7 (SLAMF7) engagement has been shown to enhance natural killer cell degranulation. This study was undertaken to characterize the expression and function of SLAMF7 on CD8+ T cell subsets isolated from the peripheral blood of SLE patients and healthy subjects. Methods: CD8+ T cell subset distribution, SLAMF7 expression, and expression of cytolytic enzymes (perforin, granzyme A [GzmA], and GzmB) on cells isolated from SLE patients and healthy controls were analyzed by flow cytometry. CD107a expression and interferon‐γ (IFNγ) production in response to viral antigenic stimulation in the presence or absence of an anti‐SLAMF7 antibody were assessed by flow cytometry. Antiviral cytotoxic activity in response to SLAMF7 engagement was determined using a flow cytometry–based assay. Results: The distribution of CD8+ T cell subsets was altered in the peripheral blood of SLE patients, with a decreased effector cell subpopulation. Memory CD8+ T cells from SLE patients displayed decreased amounts of SLAMF7, a surface receptor that characterizes effector CD8+ T cells. Ligation of SLAMF7 increased CD8+ T cell degranulation capacity and the percentage of IFNγ‐producing cells in response to antigen challenge in SLE patients and healthy controls. Moreover, SLAMF7 engagement promoted cytotoxic lysis of target cells in response to stimulation with viral antigens. Conclusion: CD8+ T cell activation in response to viral antigens is defective in SLE patients. Activation of SLAMF7 through a specific monoclonal antibody restores CD8+ T cell antiviral effector function to normal levels and thus represents a potential therapeutic option in SLE.